The Impact Of Training And Human Resource Development On Employee Productivity At The BPKAD Office In Bengkulu City - Mestri Afrita; Sri Ekowati (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to investigate the influence of training and human resource development on employee productivity at the BPKAD Office in Bengkulu City, both partially and simultaneously. The study focuses on various factors, including training and human resource development, utilizing a quantitative research approach. The research targets 50 employees of the BPKAD Office in Bengkulu City. Data collection methods include observation, interviews, and questionnaires. Analytical techniques involve instrument testing, classical assumption testing, respondent response analysis, multiple linear regression analysis, determination coefficient analysis, and hypothesis testing. Results indicate that training has a positive and significant impact on the productivity of BPKAD Office employees in Bengkulu City. Conversely, human resource development shows a negative and significant influence on employee productivity. Therefore, it can be concluded from the research that both training and human resource development have a partial and simultaneous impact on employees at the BPKAD Office in Bengkulu City.